Estudo da atividade reprodutiva de hyla truncata Izecksohn, 1959 (Anura, Hylidae) na Restinga de Maricá, RJ - Pereira, Mônica Cox de Britto (1991)
The reproductive cycle of Hyla truncata Izecksohn, 1959, was studied based on specimens collected monthly from September 1986 to August 1988. The body, ovaries, oviducts, and fat bodies weights were recorded for each animal. The ovaries and testes were fixed for histological assessment of maturity condition. Organs weights were expressed as percentage of body weight, and treated as IGS (ovary), IOV (oviduct) and ICA (fat body), The testes weights were always lower than 0.01g, while ovaries, oviducts and fat bodies weights underwent considerable changes in the seasons. No marked annual cycle was observed , however some specimens with the highest values of IGS, IOV and ICA were basically found in the rainy season of the two years studied. No inverse correlation was obtained between ovary and fat body weight , like many anurans from temperate zone. The results suggest that fat body changes were not influenced directly by reproduction, and probably varied due to nutrition. Spermatogenesis and ovogenesis were continuous, and the treefrogs were physiologically capable of reproduction throughout the year. Pos-ovulatory follicules in the ovaries and * empty tubules in the testes predominated in summer and fall, tadpoles and recently metamorphosed were also recorded in these seasons, suggesting a higher frequency of reproduction in the rainy seasons. However, late gonad stage was also found in the winter indicating that reproduction can also occur throughout the year.